Intrinsic foot muscle volume in experienced runners with and without chronic plantar fasciitis. Issue 9 (September 2016) - Cheung, R.T.H.; Sze, L.K.Y.; Mok, N.W.; Ng, G.Y.F.
Abstract: Objectives: Plantar fasciitis, a common injury in runners, has been speculated to be associated with weakness of the intrinsic foot muscles. A recent study reported that atrophy of the intrinsic forefoot muscles might contribute to plantar fasciitis by destabilizing the medial longitudinal arch. However, intrinsic foot muscle volume difference between individuals with plantar fasciitis and healthy counterparts remains unknown. This study examined the relationship of intrinsic foot muscle volume and incidence of plantar fasciitis. Design: Case-control study. Methods: 20 experienced (≥5 years) runners were recruited. Ten of them had bilateral chronic (≥2 years) plantar fasciitis while the others were healthy characteristics-matched runners. Intrinsic muscle volumes of the participants' right foot were scanned with a 1.5 T magnetic resonance system and segmented using established methods. Body-mass normalized intrinsic foot muscle volumes were compared between runners with and without chronic plantar fasciitis. Results: There was significant greater rearfoot intrinsic muscle volume in healthy runners than runners with chronic plantar fasciitis (Cohen's d = 1.13; p = 0.023). A similar trend was also observed in the total intrinsic foot muscle volume but it did not reach a statistical significance (Cohen's d = 0.92; p = 0.056). Forefoot volume was similar between runners with and without plantar fasciitis. Conclusions: These results suggest that atrophy of intrinsic foot muscles may be associated with symptoms of plantar fasciitis in runners. These findings may provide useful information in rehabilitation strategies of chronic plantar fasciitis.